CCL20/Macrophage Inflammatory Protein 3α and Tumor Necrosis Factor Alpha Production by Primary Uterine Epithelial Cells in Response to Treatment with Lipopolysaccharide or Pam(3)Cys - Crane-Godreau, Mardi A. (American Society for Microbiology, 2005)
Having previously shown that CCL20/macrophage inflammatory protein 3α and tumor necrosis factor alpha (TNF-α) are released by polarized primary rat uterine epithelial cells (UEC) in response to Escherichia coli but not to Lactobacillus rhamnosus, we sought to determine if epithelial cells are responsive to pathogen-associated molecular patterns (PAMP), including lipopolysaccharide (LPS), lipoteichoic acid (LTA), and Pam(3)Cys, a bacterial lipoprotein analog. Epithelial cells were grown to confluence on Nunc cell culture inserts prior to apical treatment with PAMPs. In response to LPS, LTA, and Pam(3)Cys (EMC Microcollection GmbH, Tübingen, Germany), CCL20 levels increased (4- to 10-fold) while PAMPs caused increased TNF-α (1- to 4-fold) in the medium collected after 24 h of incubation. Both apical and basolateral secretion of CCL20 and TNF-α increased in response to PAMPs, but treatments had no effect on cell viability and integrity, as measured by transepithelial resistance. Time course studies of CCL20 and TNF-α release in response to Pam(3)Cys and LPS indicated that CCL20 release peaked between 2 and 4 h after treatment, whereas TNF-α release was gradual over the length of the incubation. Freeze-thaw and cell lysis experiments, along with actinomycin D studies, suggested that CCL20 and TNF-α are synthesized in response to PAMP stimulation. Taken together, these studies demonstrate that E. coli and selected PAMPs have direct effects on the production of CCL20 and TNF-α without affecting cell integrity. Since CCL20 is known to be both chemotactic and antimicrobial, the increase in apical and basolateral release by UEC in response to PAMPs suggests a new mechanism of innate immune protection in the female reproductive tract.